“Stille as ston”: Oriental deformity in "The King of Tars" - Czarnowus, Anna (Adam Mickiewicz University, 2008)
The article discusses the monstrous birth in the context of the father’s conversion in the thirteenth- century King of Tars. Miscegenation has to be diagnosed as the source of the child’s shapelessness, while the topic of false accusations of monstrosity in what Margaret Schlauch termed the “accused queens” narratives, i.e. the Constance-Group, cannot be disregarded, either. In the Middle English romance bestial, and specifically mostly canine metaphors dominate in the portrayal of the sultan; yet, they turn out to be inadequate once he is baptized and undergoes magic beautification, similarly to his offspring, now endowed with a form. The work’s didactic design consists in preaching the necessity of conversion to Christianity, while the threat posed by Islam materializes in the monstrous offspring of oriental origin.